Woody Vegetation Composition and Structure in Peri-urban Chongming Island, China (2013)
Chongming, the world’s largest alluvial island, is located within the municipality of Shanghai, China. Recent projects have now linked peri-urban Chongming to Shanghai’s urban core and as a result will soon undergo substantial changes from urbanization. We quantitatively analyzed the structure and composition of woody vegetation across subtropical, peri-urban Chongming as a basis for sustainable management of these rapidly urbanizing subtropical ecosystems elsewhere. We used 178 permanent, random plots to statistically and spatially analyze woody plant composition and tree structure across the 1,041 km2 of Chongming. A total of 2,251 woody plants were measured comprising 42 species in 37 genera. We statistically and geospatially analyzed field data according to land uses and modeled air pollution removal by trees. Average tree diameter at breast height, total height, and crown widths on transportation land uses were greater than other land uses. These same values were lowest on forest land use and greater tree cover was associated with areas of increased anthropogenic activity. Less than 20 % of the woody vegetation was exotic and a species richness index was significantly different between land uses due to legacy effects. Composition of agriculture and forest land uses were similar to residential and transportation. Tree cover across Chongming was also estimated to annually remove 1,400 tons of air pollutants. We propose that this integrated and quantitative method can be used in other subtropical, peri-urban areas in developing countries to establish baseline trends for future sustainability objectives and to monitor the effects of urbanization and climate change.